Vídeo especular - Gaede, Tobias Sandino (2011)
This research analyzes the videoinstallation “Trindade”, recognizing in it the aspects of trinitarian composition of their conceptual elements (triads theoretical categorization, dialectical method, trinitarian theology) and materials (equipment, methods of image generation, optical phenomena and the production of synthetic color), and establish parallels between the image generated by it and the image produced by the tool of the mirror.